Role of Calamba City Local School Board in Good Governance (Center for Risk Management & Sustainability and RSF Press, 2023)
This study looked into the lived experiences of seven members of the Calamba Local School Board (LSB) in regard to their role in good governance. A proposal to reformulate the LSB clause in the Local Government Code was proposed as a guide for policymakers to adopt reforms in the body as a result of this study. This study used a qualitative research approach based on phenomenology. The ten superordinate themes identified through thematic analysis were Constituent Needs, External Motivators, Different People Providing Assistance, Various Perceptions on Helpful Inputs, Roles of LSB Members, Good Governance Practices, Positive Feelings, Different Challenges, and Varied Solutions. The first theme explored the role of the LSB members in ensuring transparency and accountability. The second theme showed how the members of the LSB ensured that the needs of the constituents were responded to. As for the third theme, it enumerated what made them motivated in ensuring good governance. The fourth theme elaborated on who helped them in ensuring good governance, meanwhile the fifth theme elaborated on how they perceived their help in ensuring good local governance. The sixth and seventh theme revealed their roles in the LSB in ensuring good and effective governance. The eight theme revealed the positive feelings of the members of the LSB when they were able to provide good governance. The ninth and the tenth theme revealed various challenges faced by the LSB as well as steps taken by its members in solving those challenges.